Hypoxia disturbs the Migration and Adhesion characteristics of Mesenchymal Stem Cells - Khasawneh, Ramada R.; Abu-El-Rub, Ejlal (Cellular and Molecular Biology, 2022)
Mesenchymal stem cells (MSCs) have been successfully used in treating many diseases which being verified by many preclinical and clinical trials. Despite the exciting therapeutic potential of MSCs, multiple challenges encountered which hinder researchers from achieving successful clinical translations. Many studies have showed that moderate hypoxia (1-7% O2) considered as an important regulator of MSCs homing, migration, and differentiation. Additionally, low oxygen tension levels have been implicated in the maintenance of MSCs quiescence and plasticity in general. On the other hand, severe hypoxia (<1% O2) negatively affects the in vitro therapeutic potential of MSCs and causing their poor survival. Using Elisa assay we assessed some major adhesion markers that are known to be secreted by MSCs and play a role in cell-cell and cell-matrix adhesion under normoxia (21% O2) and severe hypoxia (0.5% O2). These markers including: SDF1-α, CXCR4, FAK, VEGF and ICAM-1. The results showed a significant drop in the adhesion markers in MSCs under severe hypoxia in comparing to normoxia, which causes a disruption in the cell-cell adhesion abilities of MSCs and ultimately can affect the incorporation of MSCs at the host site. These Findings can open new avenue to improve the attachment of MSCs at the transplantation site by targeting the adhesion and chemokines markers.